Developmental considerations in youth athlete burnout: A model for youth sport participants - Harris, B. S.; Watson, J. C. (Journal of Clinical Sport Psychology, 2014)
Recent research has used self-determination theory to examine athlete burnout among adults. However, there is a dearth of theory-driven research investigating burnout among young athletes, particularly as it pertains to its sociological influences. With research suggesting that motives for sport (dis)continuation vary among athletes of different ages, this study assessed the utility of self-determination theory (SDT) and Coakley`s model for youth burnout while examining developmental differences. Participants included swimmers of ages 7-17. Analyses revealed a model that approached adequate fit indices and accounted for 70% of the burnout variance. Results supported utilizing these theories to understand youth burnout while accounting for developmental differences.